A Minimal Set of SNPs for the Noninvasive Prenatal Diagnosis of β‐Thalassaemia. (31st January 2013) - Papasavva, Thessalia E.; Lederer, Carsten W.; Traeger‐Synodinos, Jan; Mavrou, Ariadne; Kanavakis, Emmanuel; Ioannou, Christiana; Makariou, Christiana; Kleanthous, Marina
Summary β‐thalassaemia is one of the commonest autosomal recessive single‐gene disorders worldwide. Prenatal tests use invasive methods, posing a risk for the pregnancy itself. Development of a noninvasive prenatal diagnostic method is, therefore, of paramount importance. The aim of the present study is to identify high‐heterozygote informative single‐nucleotide polymorphisms (SNPs), suitable for the development of noninvasive prenatal diagnosis (NIPD) of β‐thalassaemia. SNP genotyping analysis was performed on 75 random samples from the Cypriot population for 140 SNPs across the β‐globin cluster. Shortlisted, highly heterozygous SNPs were then examined in 101 carrier families for their applicability in the noninvasive detection of paternally inherited alleles. Forty‐nine SNPs displayed more than 6% heterozygosity and were selected for NIPD analysis, revealing 72.28% of the carrier families eligible for qualitative SNP‐based NIPD, and 92% for quantitative detection. Moreover, inference of haplotypes showed predominant haplotypes and many subhaplotypes with sufficient prevalence for diagnostic exploitation. SNP‐based analyses are sensitive and specific for the detection of the paternally inherited allele in maternal plasma. This study provides proof of concept for this approach, highlighting its superiority to NIPD based on single markers and thus providing a blueprint for the general development of noninvasive prenatal diagnostic assays for β‐thalassaemia.